2018
DOI: 10.1111/jph.12712
|View full text |Cite
|
Sign up to set email alerts
|

Biological control potential of plant growth‐promoting rhizobacteria suppression of Meloidogyne incognita on cotton and Heterodera glycines on soybean: A review

Abstract: Over the past decade, we have seen an increasing market for biopesticides and an increase in number of microbial control studies directed towards plant‐parasitic nematodes. This literature survey provides an overview of research on biological control of two economically important plant‐parasitic nematodes, Meloidogyne incognita (Kofoid & White) Chitwood (southern root‐knot nematode) and Heterodera glycines Ichinohe (soybean cyst nematode) using spore‐forming plant growth‐promoting rhizobacteria (PGPR). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 56 publications
0
63
0
Order By: Relevance
“…P . lilacinus is well known for its applications in the biocontrol of Heterodera glycines in soybean and Meloidogyne incognita in cotton (Anastasiadis, Giannakou, Prophetou‐Athanasiadou, & Gowen, ; Xiang, Lawrence, & Donald, ). Wei et al (), using a culture‐based method, also detected a relatively high abundance of P .…”
Section: Discussionmentioning
confidence: 99%
“…P . lilacinus is well known for its applications in the biocontrol of Heterodera glycines in soybean and Meloidogyne incognita in cotton (Anastasiadis, Giannakou, Prophetou‐Athanasiadou, & Gowen, ; Xiang, Lawrence, & Donald, ). Wei et al (), using a culture‐based method, also detected a relatively high abundance of P .…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative bacteria, such as Pseudomonads, Burkholderia, Arthrobacter, Achromobacter, and Rhizobium spp., are reported (Antoun 2013;Sidhu 2018;Sohrabi et al 2018). Gram-positive bacteria such as Brevibacterium, Corynebacterium, Micrococcus, Bacillus, Paenibacillus, and Sarcina are also reported (Lee and Kim 2016;Rika et al 2017;Sohrabi et al 2018;Xiang et al 2018). However, in this study, the six bacterial strains identified as Bacillus, Paenibacillus, and Lysinibacillus (Grampositive bacteria) and Pseudomonas and Achromobacter (Gram-negative bacteria) may indicate the predominance of such genera in the soil as PGPR and could be good factors for suppressing the population density of Meloidogyne spp.…”
Section: Discussionmentioning
confidence: 98%
“…The most affected stages of plant-parasitic nematodes are the egg and the second-stage juvenile. To manage with biological control, these two stages of the plantparasitic nematodes should be controlled, so that the life cycle of nematodes could be interrupted, resulting in a reduction of nematode populations (Xiang et al 2018). When come in contact with the parasite nematodes, microorganisms release lytic enzymes for effective degradation of egg shell, suppression of egg hatching, and/or inhibition of nematode activity (Xiang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several Bacillus spp. have been reported in association to PPNs worldwide, and it is likely that, due to the wide diversity of this bacterial clade, new species or taxa specialized in nematode parasitism or plant growth promotion may be discovered in newly sampled areas [54][55][56].…”
Section: Discussionmentioning
confidence: 99%